Cu(OTf)(2) or Et3N-catalyzed three-component condensation of aldehydes, amines and cyanides: a high yielding synthesis of alpha-aminonitriles - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Tetrahedron Letters, 2006)
Copper(II) triflate or Et3N have been found to catalyze, under ambient conditions, the addition of a cyanide anion, such as trimethylsilyl cyanide or acetone cyanohydrin, onto in situ generated imines, furnishing alpha-aminonitriles in excellent yields. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; aminonitriles; multicomponent reactions; organocatalyst; Strecker reaction

Enantioselective synthesis of (-)-cytoxazone and (+)-epi-cytoxazone, novel cytokine modulators via sharpless asymmetric epoxidation and L-proline catalyzed mannich reaction - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Tetrahedron, 2006)
A short and efficient enantioselective synthesis of (-)-cytoxazone and its stereoisomer (+)-epi-cytoxazone, novel cytokine modulators, has been described with good yield and enantioselectivity. Ti-catalyzed Sharpless asymmetric epoxidation of allyl alcohol and L-proline catalyzed three-component Mannich reaction constitute the key steps in introducing stereogenicity into the molecule. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: aminohydroxylation; Asymmetric synthesis; epoxidation; Mannich reaction; Oxidation; Ozonolysis

Enantioselective synthesis of (S,S)-ethambutol using proline-catalyzed asymmetric alpha-aminooxylation and alpha-amination - Kotkar, Shriram P.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2006)
An efficient enantioselective synthesis of (S,S)-ethambutol, a tuberculostatic antibiotic, has been achieved in 99% ee via both proline-catalyzed alpha-aminooxylation and alpha-amination of n-butyraldehyde as the key step. (c) 2006 Elsevier Ltd. All rights reserved.

NaIO4/KI/NaCl: a new reagent system for iodination of activated aromatics through in situ generation of iodine monochloride - Emmanuvel, Lourdusamy; Shukla, Ravi Kant; Sudalai, Arumugam; Gurunath, Suryavanshi; Sivaram, Swaminathan (Tetrahedron Letters, 2006)
A new reagent system consisting of NaIO4/KI/NaCl in aq AcOH has been found to be effective in iodinating a variety of activated aromatic substrates via in situ-generated iodine monochloride, to furnish iodoaromatics in excellent yields. This iodination procedure has been applied successfully for a cost-effective synthesis of 3,3'-diaminobenzidine, a key intermediate for preparing proton conducting membranes for fuel cell applications, with high yield and a purity of 99.7%. (c) 2006 Elsevier Ltd. All rights reserved.

NaIO4-mediated selective oxidation of alkylarenes and benzylic bromides/alcohols to carbonyl derivatives using water as solvent - Ali Shaikh, Tanveer Mahammad; Emmanuvel, Lourdusamy; Sudalai, Arumugam (Journal of Organic Chemistry, 2006)
A new transition-metal-free, sodium metaperiodate (NaIO4)-mediated direct oxidation of methylarenes and benzylic bromides to the corresponding aromatic carboxylic acids is described. Under the same reaction conditions, benzylic alcohols are selectively oxidized to afford the corresponding aldehydes in good yields without undergoing overoxidation. Unprecedentedly, oxidation of benzyl bromide, toluene, or benzyl alcohol with NaIO4 underwent nuclear bromination followed by oxidation to give 4-bromobenzoic acid in 60-79% yields.

Short and practical enantioselective synthesis of linezolid and eperezolid via proline-catalyzed asymmetric alpha-aminooxylation - Narina, Srinivasarao V.; Sudalai, Arumugam (Tetrahedron Letters, 2006)
An efficient enantioselective synthesis of the antibacterials, linezolid (U-100766), and eperezolid (U-100592) using D-proline-catalyzed asymmetric alpha-aminooxylation of aldehydes as the key step is described here. This is the first report on the enantioselective synthesis of linezolid and eperezolid using asymmetric catalysis. (c) 2006 Elsevier Ltd. All rights reserved.

Short enantioselective synthesis of the antiepileptic agent, levetiracetam based on proline-catalyzed asymmetric alpha-aminooxylation - Kotkar, Shriram P.; Sudalai, Arumugam (Tetrahedron Letters, 2006)
An efficient enantioselective synthesis of a new antiepileptic drug, levetiracetam is described, in high optical purity (> 99.5% ee), using proline-catalyzed alpha-aminooxylation of n-butyraldehyde as the key step. (c) 2006 Elsevier Ltd. All rights reserved.

Cu(OTf)(2) catalyzed high yield synthesis of hantzsch 1,4-dihydropyridines - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2007)
Copper(II) triflate catalyzes efficiently the three-component condensation of aldehydes, beta-ketoesters and ammonium acetate in acetonitrile at 25 degrees C to afford the corresponding Hantzsch 1,4-dihydropyridines in high yields.
Keywords: 4-dihydropyridines; anti-hypertensive drug; calcium channel blockers; cardiovascular diseases; Hantzsch 1; three-component condensation

Efficient organocatalytic route to the atorvastatin side-chain - George, Shyla; Sudalai, Arumugam (Tetrahedron Letter, 2007)
An organocatalytic route to the synthesis of the atorvastatin side-chain, a building block present in the statin family, is described using L-proline-catalyzed alpha-aminooxylation of an aldehyde. The method also employs an iodine-induced intramolecular electrophilic cyclization of a carbonate to produce the iodocarbonate in a highly diastereoselective manner. (C) 2007 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of (-)-cytoxazone and (+)-epi-cytoxazone via Rh-catalyzed diastereoselective oxidative C-H aminations - Narina, Srinivasarao V.; Kumar, Talluri Siva; George, Shyla; Sudalai, Arumugam (Tetrahedron Letter, 2007)
An efficient enantioselective synthesis of (-)-cytoxazone (1) and (+)-epi-eytoxazone (2) using proline-catalyzed asymmetric alpha-amino-oxylation of aldehydes followed by Rh-catalyzed diastereoselective oxidative C-H amination as the key steps is described. syn or anti 1,2-aminoalcohols were obtained by Rh-catalyzed intramolecular amidation of the C-H bonds of carbamates or sulfamate esters with good to excellent diastereoselectivity. (c) 2006 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of (S)-timolol via kinetic resolution of terminal epoxides and dihydroxylation of allylamines - Narina, Srinivasarao V.; Sudalai, Arumugam (Tetrahedron, 2007)
An efficient enantioselective synthesis of (S)-timolol has been described using chiral Co-salen-catalyzed kinetic resolution of less expensive (+/-)-epichlorohydrin with 3-hydroxy-4-(N-morpholino)-1,2,5-thiadiazole in good overall yield (55%) and excellent enantioselectivity (98%). Synthesis of (S)-timolol has also been achieved using hydrolytic kinetic resolution as well as asymmetric dihydroxylation routes in 90% ee and 56% ee, respectively. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: asymmetric reactions; diols; epoxides; Kinetic resolution; oxazolidinone

NaIO4/LiBr-Mediated direct conversion of benzylic alcohols and aromatic aldehydes to aromatic esters - Shaikh, Tanveer Mohammad Ali; Emmanuvel, Lourdusamy; Sudalai, Arumugam (Synthetic Communications, 2007)
Aromatic aldehydes or benzylic alcohols are directly converted to the corresponding aromatic esters in high yields on treatment with methanol or ethanol mediated by sodium metaperiodate (NaIO4)/LiBr in an acidic medium.
Keywords: aromatic ester; benazaldehyde; Benzyl alcohol; Lithium bromide; Sodium metaperiodate

NaIO4-mediated asymmetric bromohydroxylation of alpha,beta-unsaturated carboxamides with high diastereoselectivity: a short route to (-)-cytoxazone and droxidopa - George, Shyla; Narina, Srinivasarao V.; Sudalai, Arumugam (Tetrahedron Letter, 2007)
The NaIO4-mediated asymmetric bromohydroxylation of alpha,beta-unsaturated carboxamides was achieved using lithium bromide as the bromine source under acidic conditions at rt to afford the corresponding chiral alpha-bromo-beta-hydroxy carboxamides. Excellent yields (77-90%) and diastereoselectivities (up to 10:1) along with exclusive control over regio- as well as anti-selectivity are the main features with a good scope of substrates. The method has successfully been applied in the enantioselective syntheses of two biologically important molecules, viz (-)-cytoxazone and L-threo-DOPS (droxidopa). (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: asymmetric bromohydroxylation; Carboxamide; cytoxazone; droxidopa; NaIO4

Organo-catalytic approach to the enantioselective synthesis of (R)-selegiline - Talluri, Siva Kumar; Sudalai, Arumugam (Tetrahedron, 2007)
An efficient enantioselective synthesis of (R)-selegiline has been achieved by two routes, via proline-catalyzed alpha-aminooxylation as well as alpha-amination of phenylpropanaldehyde as the key step. (c) 2007 Elsevier Ltd. All rights reserved.

Organocatalytic sequential alpha-amination-horner-wadsworth-emmons olefination of aldehydes: enantioselective synthesis of gamma-amino-alpha,beta-unsaturated esters - Kotkar, Shriram P.; Chavan, Vilas B.; Sudalai, Arumugam (Organic Letters, 2007)
A novel and highly enantioselective method for the synthesis of gamma-amino-alpha,beta-unsaturated esters via tandem alpha-amination-Horner-Wadsworth-Emmons (HWE) olefination of aldehydes is described. The one-pot assembly has been demonstrated for the construction of functionalized chiral 2-pyrrolidones, subunits present in several alkaloids.

Phosphine ligand and base-free, Pd-catalyzed oxidative cross-coupling reaction of arylboronic acids with arylmercuric acetates - Emmanuvel, Lourdusamy; Sudalai, Arumugam (Arkivoc, 2007)
Arylmercuric acetates have been found to undergo Suzuki type cross coupling reactions with arylboronic acids catalyzed by palladium salts in non-polar solvents under ambient conditions to give biaryl derivatives in high yields. The reaction is mild and does not require any organic or inorganic base nor a phosphine ligand.
Keywords: Arylboronic acid; arylmercuric acetate; palladium salts; Suzuki coupling

Co-catalyzed mild and chemoselective reduction of phenyl esters with NaBH(4): a practical synthesis of (R)-tolterodine - Jagdale, Arun R.; Sudalai, Arumugam (Tetrahedron Letters, 2008)
CoCl(2) catalyzes effectively the chemoselective reduction of phenyl carboxylic esters to the corresponding saturated alcohols in high yields using NaBH(4) at ambient conditions. By employing this methodology, the synthesis of (R)-tolterodine, a muscarinic receptor antagonist, has been achieved in high yield and optical purity. (C) 2008 Elsevier Ltd. All rights reserved.

Cu(OTf)(2) catalyzed Biginelli type condensation of aldehydes, beta-keto esters and carbamates: synthesis of 3,4-dihydro[1,3]oxazin-2-ones - Jagdale, Arun R.; Paraskar, Abhimanyu S.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2008)
Cu(OTf)(2) catalyzes effectively a new multicomponent reaction comprising aldehydes, beta-ketoester and methy carbamate in acetonitrile to afford substituted 3,4-dihydro[1,3]oxazin-2-ones in 60-82% yields. These compounds have been found to show inhibition activity against HL-60 cancer cell.
Keywords: aldehydes; Catalysts; Copper; Multicomponent reaction

NaIO4-KI-NaN3 as a new reagent system for C-H functionalization in hydrocarbons - Chouthaiwale, Pandurang V.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2008)
The NaIO4-KI-NaN3 combination has been found to be an efficient, reliable, and inexpensive reagent system for mono- and 1,2-difunctionalization of hydrocarbons via C-H bond activation to afford vicinal azido- and acetoxy iodinations of cyclic hydrocarbons. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: azides; C-H activation; Iodination; NaIO4

Short enantioselective synthesis of (-)-bestatin via L-proline-catalyzed alpha-amination of an aldehyde - George, Shyla; Suryavanshi, Gurunath S.; Sudalai, Arumugam (Tetrahedron Letters, 2008)
A short and high yielding enantioselective synthesis of (-)-bestatin, a naturally occurring aminopeptidase inhibitor, is described Via L-proline-catalyzed asymmetric alpha-amination of 3-phenylpropionaldehyde as the key reaction. The methodology also involves a Pd-catalyzed intramolecular cyclization of an allylic acetate giving a trans-oxazoline in a highly diastereoselective manner (dr > 14:1). (C) 2008 Elsevier Ltd. All rights reserved.

Short enantioselective synthesis of (+)-L-733,060 via Shi epoxidation of a homoallylic carboxylate - Emmanuvel, Lourdusamy; Sudalai, Arumugam (Tetrahedron Letters, 2008)
A short and efficient enantioselective synthesis of (+)-L-733,060 in 92% ee via Shi epoxidation of a homoallylic carboxylate is described. Johnson-Claisen rearrangement was employed to obtain the required carbon backbone, whilst intramolecular reductive O-to-N-ring expansion of a delta-azidolactone was used in the construction of the piperidine moiety. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: 1; 2-aminoalcohols; 3; 3-sigmatropic rearrangement; asymmetric epoxidation; Lactone

WO3/70% TBHP/aqueous NaOH: an efficient catalytic combination for the selective oxidation of methylarenes and alkyl aryl ketones to benzoic acids - Shaikh, Tanveer Mahammad Ali; Sudalai, Arumugam (European Journal of Organic Chemistry, 2008)
A new solvent-free, reusable catalytic combination consisting Of WO3/70% TBHP/aqueous NaOH has been described for the direct oxidation of methylarenes and acetophenones to the corresponding benzoic acids in high yields. Alkylarenes are oxidized to the corresponding aromatic ketones or benzylic alcohols depending upon whether NaOH is used or not. ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Keywords: Arenes; Benzoic acids; Ketones; Oxidation; Tungsten

Asymmetric synthesis of tetrahydroquinolin-3-ols via CoCl2-catalyzed reductive cyclization of nitro cyclic sulfites with NaBH4 - Jagdale, Arun R.; Reddy, R. Santhosh; Sudalai, Arumugam (Organic Letters, 2009)
A new method for the construction of chiral 3-substituted tetrahydroquinoline derivatives based on asymmetric dihydroxylation and CoCl2-catalyzed reductive, cyclization of nitro cyclic sulfites with NaBH4 has been described with high optical purities. This method has been successfully applied in the formal synthesis of PNU 95666E and anachelin H chromophore.

Cobalt(II) chloride hexahydrate-diisopropylamine catalyzed mild and chemoselective reduction of carboxylic esters with sodium borohydride - Jagdale, Arun R.; Paraskar, Abhimanyu S.; Sudalai, Arumugam (Synthesis-Stuttgart, 2009)
The cobalt-catalyzed reduction of unsaturated alpha-cyano carboxylic esters using sodium borohydride (NaBH(4)) leads to the corresponding saturated cyano alcohols in high yields. In particular, the new catalytic system cobalt(II) chloride-diisopropylamine in combination with NaBH(4) showed excellent activity in the chemoselective reduction of a variety of carboxylic esters to their corresponding alcohols in good to excellent yields under mild conditions.
Keywords: Alcohols; amines; catalysis; Esters; reductions

Concise enantioselective synthesis of (+)-decarestrictine L via proline-catalyzed sequential alpha-aminooxylation and Horner-Wadsworth-Emmons olefination - Rawat, Varun; Chouthaiwale, Pandurang V.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2009)
A short enantioselective synthesis of (+)-decarestrictine L, a cholesterol biosynthesis inhibitor metabolite, is described using a D-proline catalyzed sequential alpha-aminooxylation and a Horner-Wadsworth-Emmons olefination. (C) 2009 Elsevier Lid All rights reserved

Concise enantioselective synthesis of (+)-febrifugine - Emmanuvel, Lourdusamy; Kamble, Dayanand A.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2009)
A short enantioselective synthesis of (+)-febrifugine, a potent antimalarial alkaloid, has been described based on the regioselective asymmetric dihydroxylation of a 1,4-dienic ester as the key step. The strategy also involves chemoselective [3,3]-sigmatropic rearrangement of 1,5-hexadiene-3-ol and intramolecular lactamization of azidolactone for the construction of piperidine core. (C) 2008 Elsevier Ltd. All rights reserved.

Concise enantioselective synthesis of (+)-lentiginosine - Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2009)
A high yielding enantioselective synthesis of the indolizidine alkaloid, (+)-lentiginosine, has been described based on asymmetric oza-Cope rearrangement and the L-proline catalyzed alpha-aminooxylation of aldehydes. The strategy also makes use of ring-closing metathesis for the construction of piperidine core. (C) 2009 Elsevier Ltd. All rights reserved.

Cu(OTf)(2)-catalyzed alpha-halogenation of ketones with 1,3-dichloro-5,5 `-dimethylhydantoin and N-bromosuccinimide - Jagdale, Arun R.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2009)
Copper(II) triflate catalyses efficiently the alpha-halogentation of aryl or alkyl ketones with 1,3-dichloro-5,5'-dimethyl-hydantoin and N-bromosaccinimde to give the corresponding alpha,alpha-dichloroketones and alpha-bromoketones in high yield with excellent product selectivity.
Keywords: Bromination; Catalyst; chlorination; copper (II); Ketone; Lewis acid

Formal synthesis of (-) anisomycin via organocatalysis - Chouthaiwale, Pandurang V.; Kotkar, Shriram P.; Sudalai, Arumugam (Arkivoc, 2009)
An efficient formal synthesis of (-) anisomycin (1), a potent antibiotic agent, has been achieved in good yields and excellent diastereoselectivity. The key steps are proline-catalyzed sequential alpha-amination or alpha-aminoxylation of aldehyde 2 followed by tandem Horner-Wadsworth-Emmons olefination.
Keywords: alpha-Amination; alpha-aminoxylation; anisomycin; olefination; Proline

Titanium superoxide: a heterogeneous catalyst for anti-Markovnikov aminobromination of olefins - Shaikh, Tanveer Mahamadali; Karabal, Pratibha U.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2009)
A new facile procedure for the aminobromination of olefins in high yields has been described using p-toluene sulfonamide (p-TsNH(2)) and N-bromosuccinimide (NBS) as introgen and bromine sources, respectively, and titanium superoxide as a truly heterogeneous catalyst. The formation of anti-Markovnikov product exclusively in all the cases studied possibly proceeding I free radical reaction pathway is remarkable. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: anti-Markovnikov addition; Bromoamination; N-Bromosuccinimide; p-Toluenesulfonamide; Titanium superoxide

Co(III)(salen)-catalyzed HKR of two stereocentered alkoxy- and azido epoxides: a concise enantioselective synthesis of (S,S)-reboxetine and (+)-epi-cytoxazone - Reddy, R. Santhosh; Chouthaiwale, Pandurang V.; Suryavanshi, Gurunath; Chavan, Vilas B.; Sudalai, Arumugam (Chemical Communications, 2010)
The HKR of racemic syn- or anti- alkoxy- and azido epoxides catalyzed by Co(salen) complex affords a practical access to a series of enantioenriched syn- or anti- alkoxy- and azido epoxides and the corresponding 1,2-diols. This strategy has been successfully employed in the concise, enantioselective synthesis of bioactive molecules such as (S, S)-reboxetine and (+)-epi-cytoxazone.

Enantioselective synthesis of (+)-alpha-conhydrine and (-)-sedamine by L-proline-catalysed alpha-aminooxylation - Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (European Journal of Organic Chemistry, 2010)
An efficient organocatalytic approach to the enantioslective synthesis of two important piperidine alkaloids, namely (+)-alpha-conhydrine (98% ee) and (-)-sedamine (95% ee), by L-proline-catalysed alpha-aminooxylation of aldehydes has been developed. The strategy involves an intramolecular cyclization to construct the piperidine core.
Keywords: alkaloids; Amino acids; Aminooxylation; Enantioselectivity; organocatalysis

Facile enantioselective synthesis of (S)-N-(5-chlorothiophene-2-sulfonyl)-beta,beta-diethylalaninol via proline-catalyzed asymmetric alpha-aminooxylation and alpha-amination of aldehyde - Rawat, Varun; Chouthaiwale, Pandurang V.; Chavan, Vilas B.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2010)
A high-yielding enantioselective synthesis of the bioactive (S)-N-(5-chlorothiophene-2-sulfonyl)beta,beta-diethylalaninol (1), a Notch-1-sparing gamma-secretase inhibitor metabolite (with EC50 = 28 nM) effective in reduction of All production in vivo, has been realized starting from readily available 3-pentanone. The key steps of the synthesis are proline-catalyzed alpha-aminooxylation and alpha-amination of aldehyde: the latter contributing an overall yield of 45.2% and 98% ee. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: alpha-Amination; alpha-Aminooxylation; Alzheimer's disease; Amino alcohol; Proline

H-beta zeolite: an efficient, reusable catalyst for one-pot synthesis of isatins from anilines - Raj, I. Victor Paul; Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (Acta Chimica Slovenica, 2010)
We describe a simple and highly efficient procedure for the single-step preparation of isatins from the commercially available anilines using H-beta zeolite as a truly heterogeneous catalyst. H-beta zeolite is readily separated from reaction mixture by simple filtration and reused several times without considerable loss of activity.
Keywords: Anilines; H-beta zeolite; heterogeneous catalyst; isatins

NaIO4/LiBr-mediated aziridination of olefins using chloramine-T - Karabal, Pratibha U.; Chouthaiwale, Pandurang V.; Shaikh, Tanveer M.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2010)
A new milder protocol for aziridination of a variety of olefins has been described. The process employs catalytic amount of sodium metaperiodate (NaIO4) as an oxidant and LiBr and chloramine-T as the bromine and nitrogen sources, respectively. Interestingly, the formation of aziridine products in all the cases studied takes place presumably through a process of 1,2-aminobromination of alkenes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Aziridination; Chloramine-T; Lithium bromide; Olefin; Sodium metaperiodate

Novel synthesis and characterization of titanium superoxide and its application in organic oxidative processes - Reddy, R. Santhosh; Shaikh, Tanveer Mahamadali; Rawat, Varun; Karabal, Pratibha U.; Dewkar, Gajanan; Suryavanshi, Gurunath; Sudalai, Arumugam (Catalysis Surveys from Asia, 2010)
A novel, exceptionally stable titanium superoxide radical ion was prepared and its structure determined by FTIR, ESR, Raman spectroscopy, X-ray diffraction, thermogravimetric/differential thermal analysis and elemental analysis. This heterogeneous catalyst has been found to be effective for the selective oxidation of aromatic amines and phenols to the corresponding nitro aromatics and p-quinones, respectively. In addition, this non-toxic, inexpensive and reusable catalyst has also been used in aminobromination of olefins, which proceed to give the 1, 2-bromoaminated anti-Markovnikov product. A brief account of these results is summarized in this review.
Keywords: Amino Bromination; Anti-Markovnikov; heterogeneous catalyst; Oxidation; Titanium superoxide

Regiospecific azidoiodination of alkenes with sodium periodate, potassium iodide, and sodium azide: a high-yield synthesis of beta-iodoazides - Chouthaiwale, Pandurang V.; Karabal, Pratibha U.; Suryavanshi, Gurunath; Sudalai, Arumugam (Synthesis-Stuttgart, 2010)
The combination of sodium periodate, potassium iodide, and sodium azide has been found to be an efficient, simple, and inexpensive reagent system for azidoiodination of alkenes. The regiospecific 1,2-azidoiodination proceeds in an anti-Markovnikov fashion to produce beta-iodoazides in excellent yields.
Keywords: alkenes; azides; azidoiodination; beta-iodoazides; regio-specific

Short enantioselective synthesis of guggultetrol, a naturally occurring lipid - George, Shyla; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2010)
An enantioselective synthesis of the naturally occurring lipid, guggultetrol, is described with an overall yield of 24% starting from commercially available 1-pentadecanol in ten linear steps. The key chiral-inducing steps include a Sharpless asymmetric epoxidation of allylic alcohol and a dihydroxylation of an alpha,beta-unsaturated ester. (C) 2010 Elsevier Ltd. All rights reserved.

Concise enantioselective synthesis of (+)-goniodiol and (+)-8-methoxygoniodiol via Co-catalyzed HKR of anti-(2SR, 3RS)-3-methoxy-3-phenyl-1, 2-epoxypropane - Kiran, I. N. Chaithanya; Reddy, R. Santhosh; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2011)
A short, enantioselective synthesis of (+)-goniodiol and (+)-8-methoxygoniodiol, cytotoxic styryllactones, has been achieved in high optical purities (99% ee). The strategy employs Co-catalyzed HKR of racemic anti-(2SR, 3RS)-3-methoxy-3-phenyl-1,2-epoxypropane and Lewis acid-mediated diastereoselective allylation of aldehyde as chiral inducing key reactions. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Allylation; diastereoselectivity; Hydrolytic kinetic resolution; Racemic anti-epoxide; Styryllactones

Asymmetric synthesis of (+)-stagonolide C and (-)-aspinolide A via organocatalysis - Shelke, Anil M.; Rawat, Varun; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2012)
A new enantioselective synthesis of two important fungal metabolites, (+)-stagonolide C and (-)-aspinolide A, has been described from readily available raw materials. Praline catalyzed asymmetric alpha-aminooxylation and Jorgensen's epoxidation of aldehydes are the key reactions employed in the introduction of chirality. The formation of the 10-membered lactone core structure was finally accomplished via Steglich esterification and ring closing metathesis reactions. (C) 2012 Elsevier Ltd. All rights reserved.

CN-assisted oxidative cyclization of cyano cinnamates and styrene derivatives: a facile entry to 3-substituted chiral phthalides - Reddy, R. Santhosh; Kiran, I. N. Chaithanya; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2012)
The asymmetric dihydroxylation (AD) of o-cyano cinnamates and styrene derivatives leads to efficient construction of chiral phthalide frameworks in high optical purities. This unique reaction is characterized by unusual synergism between CN and osmate groups resulting in rate enhancement of the AD process. The method is amply demonstrated by the synthesis and the structural/stereochemical assignment of the natural products.

Concise synthesis of (+)-deoxoprosophylline via Co(III)(salen)-catalyzed two stereocentered HKR of racemic azido epoxides - Devalankar, Dattatray A.; Sudalai, Arumugam (Tetrahedron Letters, 2012)
An efficient synthesis of (+)-deoxoprosophylline has been achieved in high optical purity (99% ee) from readily available cis-2-butene-1,4-diol. The strategy employs Co-catalyzed Hydrolytic Kinetic Resolution (HKR) of two stereocentered racemic azido epoxides and diastereoselective intramolecular reductive cyclization as key reactions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Azido epoxide; Hydrolytic kinetic resolution; Piperidine; Wittig olefination

Cu-II-exchanged montmorillonite K10 clay-catalyzed direct carboxylation of terminal alkynes with carbon dioxide - Aher, Ravindra D.; Gade, Madhuri H.; Reddy, R. Santhosh; Sudalai, Arumugam (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
A new, simple and straight-forward protocol for direct carboxylation of terminal alkynes has been developed using Cu-II-montmorillonite K10 clay as a heterogeneous catalyst and CO2 as the C1 carbon feedstock. Also coupling of terminal alkynes with CO2 (1 atm) in the presence of alkyl halides has been achieved under the same reaction conditions, thereby providing access to a variety of functionalized alkyl-2-alkynoates in high yields.
Keywords: Alkyl esters; Alkyne C-H activation; Carbon dioxide activation; Carboxylation; Catalysts; Montmorillonite clays

Enantioselective synthesis of HIV protease inhibitor amprenavir via Co-catalyzed HKR of 2-(1-azido-2-phenylethyl)oxirane - Gadakh, Sunita K.; Reddy, R. Santhosh; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2012)
A short and efficient enantioselective synthesis of the HIV protease inhibitor amprenavir 1 (99% ee) as well as a formal synthesis of saquinavir 3 have been achieved in high enantiomeric purity starting from commercially available materials. Our strategy mainly comprises a Co-catalyzed two-stereocentred hydrolytic kinetic resolution (HKR) of racemic 2-(1-azido-2-phenylethyl)oxirane as the chirality inducing step. Also presented is a concise synthesis of (S)-3-hydroxytetrahydrofuran 4, the key structural feature, in high enantiomeric purity (98% ee). (c) 2012 Elsevier Ltd. All rights reserved.

NaIO4-NaN3-mediated diazidation of styrenes, alkenes, benzylic alcohols, and aryl ketones - Kamble, Dayanand A.; Karabal, Pratibha U.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Tetrahedron Letters, 2012)
Sodium periodate and sodium azide combination has been found to be an excellent reagent system suitable for the direct diazidation of styrenes, alkenes, benzylic alcohols, and aryl ketones to produce the corresponding vicinal and geminal diazides respectively in high yields under mild reaction conditions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: alkenes; Aryl ketones; Geminal diazides; Sodium periodate; Vicinal diazides

Organocatalytic sequential alpha-amination/corey-chaykovsky reaction of aldehydes: a high yield synthesis of 4-hydroxypyrazolidine derivatives - Kumar, B. Senthil; Venkataramasubramanian, V.; Sudalai, Arumugam (Organic Letters, 2012)
A tandem reaction of in situ generated a-amino aldehydes with dimethyloxosulfonium methylide under Corey-Chaykovsky reaction conditions proceeds efficiently to give 4-hydroxypyrazolidine derivatives in high yields with excellent enantio- and diastereoselectivities. This organocatalytic sequential method provides for the efficient synthesis of anti-1,2-aminoalcohols, structural subunits present in several bioactive molecules as well.

Pd-catalyzed selective hydrosilylation of aryl ketones and aldehydes - Chouthaiwale, Pandurang V.; Rawat, Varun; Sudalai, Arumugam (Tetrahedron Letters, 2012)
Pd salts in combination with triethylsilane as hydride source and DMF as solvent has been found to be excellent catalytic combination that selectively reduces aryl ketones and aldehydes under mild conditions to afford triethylsilyloxy compounds in excellent yields. Product selectivity to the respective benzyl alcohols can however be achieved when the reaction was performed in DMF/H2O (4:1) as solvent system. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; Hydrosilylation; Ketones; Palladium; Triethylsilane

CuCN-Mediated cascade cyclization of 4-(2-bromophenyl)-2-butenoates: a high-yield synthesis of substituted naphthalene amino esters - Reddy, R. Santhosh; Prasad, Pragati K.; Ahuja, Brij Bhushan; Sudalai, Arumugam (Journal of Organic Chemistry, 2013)
A new method of CuCN-mediated one-pot cyclization of 4-(2-bromophenyl)-2-butenoates leading to efficient synthesis of substituted naphthalene amino esters including phenanthrene aromatic structural units is described. Deuterium labeling studies establish that this one-pot cascade cyclization proceeds through isomerization of olefin, intramolecular C-C bond cyclization, and aromatization as the key intermediates, all occurring in a single step.

N-Heterocyclic carbene catalyzed esterification of aromatic aldehydes with alcohols under aerobic conditions - Kiran, I. N. Chaithanya; Lalwani, Komal G.; Sudalai, Arumugam (RSC Advances, 2013)
A simple, organocatalytic procedure for the direct oxidative esterification of a variety of aromatic aldehydes with alcohols has been described that affords the corresponding aromatic esters in high yields. The method employs N-heterocyclic carbenes as catalysts and molecular O-2 as an oxidant under ambient conditions.

N-Heterocyclic carbene catalyzed oxidative stannylation of aldehydes: a facile entry to organotin(IV) carboxylates - Reddi, Rambabu N.; Malekar, Pushpa V.; Sudalai, Arumugam (Tetrahedron Letters, 2013)
A simple protocol is described for the oxidative transformation of aldehydes to the corresponding organotin(IV) carboxylates in high yields (up to 90%) that utilizes atmospheric O-2 as the sole oxidant, N-heterocyclic carbene as catalyst (at 10 mol %), and tributyl tin chloride as stannylating agent. The uniqueness of the reaction lies in the direct conversion of aldehydes to the corresponding organotin(IV) carboxylates via stannylation of carboxylic acids, generated from the reaction of a Breslow intermediate with O-2. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carboxylic acid stannanes; N-Heterocyclic carbene; Oxidative stannylation; oxygen; Tributyltin chloride

N-Heterocyclic carbene catalyzed regioselective oxo-acyloxylation of alkenes with aromatic aldehydes: a high yield synthesis of alpha-acyloxy ketones and esters - Reddi, Rambabu N.; Malekar, Pushpa V.; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2013)
An N-heterocyclic carbene (NHC)-catalyzed reaction of alkenes with aromatic aldehydes providing for a high yield synthesis of alpha-acyloxy ketones and esters has been described. This unprecedented regioselective oxidative process employs NBS and Et3N in stoichiometric amounts and O-2 (1 atm) as an oxidant under ambient conditions in DMSO as a solvent.

Optically pure gamma-butyrolactones and epoxy esters via two stereocentered HKR of 3-substituted epoxy esters: a formal synthesis of (-)-paroxetine, Ro 67-8867 and (+)-eldanolide - Devalankar, Dattatray A.; Karabal, Pratibha U.; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2013)
The HKR of racemic anti- or syn-3-substituted epoxy esters catalyzed by a Co(III)salen complex provides ready access to the corresponding enantioenriched 3,4-disubstituted gamma-butyrolactones and 3-substituted epoxy esters. This strategy has been successfully employed in the formal synthesis of biologically active 3,4-disubstituted piperidine derivatives, (-)-paroxetine and Ro 67-8867 and a natural product, (+)-eldanolide.

Proline catalyzed sequential alpha-aminooxylation or -amination/reductive cyclization of o-nitrohydrocinnamaldehydes: a high yield synthesis of chiral 3-substituted tetrahydroquinolines - Rawat, Varun; Kumar, B. Senthil; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2013)
A new sequential organocatalytic method for the synthesis of chiral 3-substituted (X = OH, NH2) tetrahydroquinoline derivatives (THQs) [ee up to 99%, yield up to 87%] based on alpha-aminooxylation or -amination followed by reductive cyclization of o-nitrohydrocinnamaldehydes has been described. This methodology has been efficiently demonstrated in the synthesis of two important bioactive molecules namely (-)-sumanirole (96% ee) and 1-[(S)-3-(dimethylamino)-3,4-dihydro-6,7-dimethoxy-quinolin-1(2H)-yl]- propanone (92% ee).

Co(III)(salen)-catalyzed phenolic kinetic resolution of two stereocentered benzyloxy and azido epoxides: its application in the synthesis of ICI-118,551, an anti-hypertensive agent - Karabal, Pratibha U.; Kamble, Dayanand A.; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2014)
The salen Co(III)-catalyzed phenolic kinetic resolution of racemic anti- or syn-azido and benzyloxy epoxides provides a practical route to a range of enantioenriched anti-or syn-1-aryloxy-3-azido or benzyloxy-2-alcohols in excellent yields and ees. The synthetic potential of this protocol is illustrated with an enantioselective synthesis of ICI-118,551, a beta-blocker, in a highly optically pure form (99% ee).

Concise enantioselective syntheses of (+)-L-733,060 and (2S,3S)-3-hydroxypipecolicw acid by cobalt(III)(salen)-catalyzed two-stereocenter hydrolytic kinetic resolution of racemic azido epoxides - Devalankar, Dattatray A.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Synlett, 2014)
An efficient synthesis of the 2,3-disubstituted piperidines (+)-L-733,060 and (2S,3S)-3-hydroxypipecolic acid (99% ee) in high optical purity from commercially available starting materials is described. The strategy involves a cobalt-catalyzed hydrolytic kinetic resolution of a racemic azido epoxide with two stereocenters and an intramolecular reductive cyclization as key reactions.
Keywords: azides; cyclizations; epoxides; piperidines; stereoselective synthesis; Wittig reactions

Copper(I) bromide-catalyzed carbonylative coupling of aryl halides with phenols, alcohols and amines using sodium cyanide as C-1 source: a synthesis of carboxylic acid derivatives - Prasad, Pragati K.; Sudalai, Arumugam (Advanced Synthesis & Catalysis, 2014)
A new ``carbon monoxide-free'' synthesis of carboxylate derivatives via carbonylative coupling of aryl bromides with phenols, alcohols, amines and acids in the presence of copper(I) bromide as catalyst and sodium cyanide in a stoichiometric amount has been developed. Its intramolecular version provides for the preparation of lactones (e.g., isochroman-1-ones and isobenzfuranones), imides, anhydrides and lactams in excellent yields (73-96%).
Keywords: anhydrides; C-1 building blocks; isochroman-1-ones; lactams; lactones

I-2-catalyzed regioselective Oxo- and hydroxy-acyloxylation of alkenes and enol ethers: a facile access to alpha-acyloxyketones, esters, and diol derivatives - Reddi, Rambabu N.; Prasad, Pragati K.; Sudalai, Arumugam (Organic Letters, 2014)
I-2-catalyzed oxo-acyloxylation of alkenes and enol ethers with carboxylic acids providing for the high yield synthesis of a-acyloxyketones and esters is described. This unprecedented regioselective oxidative process employs TBHP and Et3N in stoichiometric amounts under metal-free conditions in DMSO as solvent. Additionally, I-2-catalysis allows the direct hydroxy-acyloxylation of alkenes with the sequential addition of BH3 center dot SMe2 leading to monoprotected diol derivatives in excellent yields.

One-pot synthesis of cyclic carbonates from aldehydes, sulfur ylide, and CO2 - Aher, Ravindra D.; Kumar, B. Senthil; Sudalai, Arumugam (Synlett, 2014)
Treatment of aldehydes with sulfur ylide (CH2=SOMe2 or CH2=SMe2), in the presence of CO2 (1 atm) bubbled sequentially under mild conditions, produces cyclic carbonates in preparative yields. Sodium iodide formed in situ promotes the reaction between epoxide as intermediate and CO2 at ambient conditions, thus constituting a powerful metal-free synthesis of organic cyclic carbonates directly from aldehydes.
Keywords: Carbon dioxide; cyclic carbonates; cyclization; epoxides; Insertion

Simple and efficient synthesis of isocoumarins and alkylidenephthalides from 3-(1-hydroxycarbethoxy/alkyl)phthalides with a DEAD/PPh3/TBHP system - Gadakh, Sunita K.; Sudalai, Arumugam (RSC Advances, 2014)
A facile and novel approach to the synthesis of 3-carbethoxy-isocoumarins and 3-alkylidenephthalides is described. The methodology employs DEAD/PPh3/TBHP as the reagent system proceeding through unprecedented 1,2-shift intramolecular ring expansion or simple elimination depending upon substituents present on 3-substituted phthalides, with broader substrate scope. This strategy is amply demonstrated in the short synthesis of bioactive molecules such as cytogenin and (Z)-3-butylidene-7-hydroxy-5-methoxyphthalide.

Co-catalyzed two-stereocentered hydrolytic kinetic resolution: application to the synthesis of yashabushidiols A and B and the lactone unit of compactin and mevinolin - Gadakh, Sunita K.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
A short and efficient enantioselective synthesis of yashabushidiols A and B and the beta-hydroxy-delta-lactone moiety of compactin and mevinolin with high enantiomeric purity (98% ee) is described starting from commercially available materials. The strategy mainly comprises of iodine-induced intramolecular electrophilic addition of a carbonate occurring in a highly diastereoselective fashion and the Co-catalyzed two-stereocentered hydrolytic kinetic resolution of a functionalized epoxide as the chiral inducing step. (C) 2014 Elsevier Ltd. All rights reserved.

Concise enantioselective synthesis of (2S,3S)-3-hydroxypipecolic acid via proline catalyzed alpha-aminooxylation of aldehydes and Pd-catalyzed ether directed aza-Claisen rearrangements - Ahuja, Brij Bhushan; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
An efficient approach to (2S,3S)-3-hydroxypipecolic acid with an overall yield of 10.2% and 98% ee starting from 1,5-pentanediol has been developed. The key steps employed in the synthesis are the D-proline catalyzed sequential alpha-aminooxylation/Horner-Wadsworth-Emmons olefination of an aldehyde and the Pd-catalyzed MOM-ether directed aza-Claisen rearrangement of an allylic trichloroacetimidate. (C) 2014 Elsevier Ltd. All rights reserved.

Concise enantioselective synthesis of marine macrolide-stagonolide E via organocatalysis - Dey, Soumen; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
A short and efficient enantioselective synthesis of marine macrolide stagonolide E in high enantiomeric purity (98% ee and 8.5% overall yield) starting from commercially available raw materials has been achieved. The strategy involves proline catalyzed sequential alpha-aminooxylation and Horner-Wadsworth-Emmons olefination, highly stereoselective Ando's cis-olefination, and modified Yamaguchi macrolactonization as the key reaction steps. (C) 2015 Elsevier Ltd. All rights reserved.

Concise enantioselective synthesis of naturally active (S)-3-hydroxypiperidine - Dey, Soumen; Karabal, Pratibha U.; Sudalai, Arumugam (Synthetic Communications, 2015)
A short and efficient enantioselective synthesis of natural product (S)-3-hydroxypiperidine has been achieved starting from commercially available raw materials employing two catalytic routes: (i) cocatalyzed hydrolytic kinetic resolution (HKR) of racemic methyl-3-(oxiran-2-yl)propanoate; (ii) proline-catalyzed -aminooxylation followed by Horner-Wardsworth-Emmons olefination in high enantiomeric purity (97% ee) and high overall yield (38%).
Keywords: Asymmetric synthesis; bioactivity; Enantioselectivity; Natural products; organocatalysis

Concise enantioselective synthesis of (R)-selegiline, (S)-benzphetamine and formal synthesis of (R)-sitagliptin via electrophilic azidation of chiral imide enolates - Dey, Soumen; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
A concise and high yielding enantioselective synthesis of (R)-selegiline, an anti-Parkinson's drug, (S)-benzphetamine, an anti-obesity agent, and (S)-sitagliptin, an anti-diabetic drug has been described starting from commercially available starting materials employing Evans' electrophilic azidation of chiral imide enolates as a key chiral inducing step, which proceeds in a highly diastereoselective manner (>99%). (C) 2014 Elsevier Ltd. All rights reserved.

Concise synthesis of (+/-)-clopidogrel via carboxylation of benzylamine with CO2 - Venkataramasubramanian, V.; Sudalai, Arumugam (Synthetic Communications, 2015)
A concise and efficient synthesis of (+/-)-clopidogrel, an antithrombotic agent, is achieved by inserting CO2 at the benzylic position as the key reaction without using any toxic transition metals. The overall yield of the synthetic process is 38% and the salient features include operationally simple process chemistry and fewer steps.
Keywords: Antithrombatic agent; clopidogrel; CO2 insertion; Plavix

Cu-catalyzed debrominative cyanation of gem-dibromoolefins: a facile access to alpha,beta-unsaturated nitriles - Ahuja, Brij Bhushan; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2015)
An efficient catalytic route for the synthesis of alpha,beta-unsaturated nitriles from easily accessible gem-dibromoolefins has been developed. The method utilized inexpensive reagents such as Cu2O as a catalyst, L-proline as a ligand and NaCN as a cyanide source to afford alpha,beta-unsaturated nitriles in high yields (62-86%). A deuterium exchange study has shown that one of the bromide atoms of gem-dibromoolefins exchanges with cyanide while the other with a deuterium atom.

Enantioselective synthesis of guggultetrol and D-ribo-phytosphingosine tetraacetate via L-proline catalyzed sequential alpha-aminooxylation/Horner-Wardsworth-Emmons olefination-Sharpless asymmetric dihydroxylation strategy - Venkataramasubramanian, V.; Kumar, B. Senthil; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
An efficient enantioselective synthesis of two bioactive molecules, that is, guggultetrol and D-ribo-phytosphingosine, is described with high enantioselectivity (>98% ee) starting from commercially available 1-hexadecanol. The synthesis comprises organocatalyzed sequential alpha-aminooxylation of an aldehyde followed by Horner-Wardsworth-Emmons olefination and Sharp less asymmetric dihydroxylation as the key chiral inducing steps. For both syntheses, gamma-hydroxy-alpha,beta-unsaturated ester serves as the common intermediate obtained from proline catalysis. (C) 2015 Elsevier Ltd. All rights reserved.

First enantioselective synthesis of (2S,3S)-3-hydroxy-L-arginine via proline catalyzed alpha-aminooxylation of aldehyde and Pd-catalyzed ether-directed aza-Claisen rearrangement - Ahuja, Brij Bhushan; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
A concise enantioselective synthesis of (2S,3S)-3-hydroxy-L-arginine with an overall yield of 10.9% and 98% ee, starting from commercially available 1,4-butanediol in ten linear steps has been achieved. The key chiral inducing steps are D-proline catalyzed sequential alpha-aminooxylation/Horner-Wadsworth-Emmons olefination of an aldehyde and the subsequent diastereoselective MOM-ether-directed Pd-catalyzed aza-Claisen rearrangement of allylic trichloroacetimidate. (C) 2015 Elsevier Ltd. All rights reserved.

First enantioselective synthesis of surinamensinol B and a non-natural polysphorin analogue by a two-stereocentered hydrolytic kinetic resolution - Lalwani, Komal G.; Sudalai, Arumugam (European Journal of Organic Chemistry, 2015)
An efficient and economical approach to the synthesis of antitumor and anti-inflammatory surinamensinol B (1) and antimalarial polysphorin analogue 2 has been achieved with high enantiomeric purity (96% ee) by starting from commercially available 3,4,5-trimethoxybenzaldehyde. The key steps of the strategy include a Co-catalyzed two-stereocentered hydrolytic kinetic resolution (HKR) of racemic 2[( methoxymethoxy)(3,4,5-trimethoxyphenyl)methyl] oxirane (13) as the chiral inducing step followed by a Mitsunobu reaction. Chiral epoxide 14 and chiral diol 15 were utilized in the syntheses of both compounds.
Keywords: Biological activity; Enantioselectivity; Kinetic resolution; Natural products; Total synthesis

Highly efficient regioselective synthesis of pyrroles via a tandem enamine formation-Michael addition-cyclization sequence under catalyst- and solvent-free conditions - Vivekanand, Thavaraj; Vinoth, Perumal; Agieshkumar, B.; Sampath, Natarajan; Sudalai, Arumugam; Menendez, Carlos; Sridharan, Vellaisamy (Green Chemistry, 2015)
A convenient catalyst-free, three-component procedure was developed for the synthesis of tetrasubstituted pyrroles under solvent-free conditions and in green solvents glycerol, PEG-200 and water. A sequential enamine-formation, Michael addition and intramolecular cyclization of primary amines, 1,3-dicarbonyl compounds and isatin-derived Michael acceptors afforded 3-(1H-pyrrol-3-yl)indolin-2-ones in excellent yields. In this simple one-pot transformation the requirement of column chromatography purification of the products was completely avoided. Besides, the method is highly environmentally benign and atom-economical, and the only side product of this reaction was two molecules of water. A comparative study for the four developed conditions showed that the solvent-free conditions were superior regardless of the nature of the starting materials, and the green solvents were effective for alkyl and benzylamines affording higher yields compared to arylamines. The preliminary in vitro cytotoxic studies of a representative compound against Ehrlich's ascites carcinoma (EAC) tumor cells showed significant activity with a CTC50 value of 15.64 mu M.

N-Heterocyclic carbene catalyzed oxidative coupling of alkenes/alpha-bromoacetophenones with aldehydes: a facile entry to alpha,beta-epoxy ketones - Reddi, Rambabu N.; Prasad, Pragati K.; Sudalai, Arumugam (Angewandte Chemie-International Edition, 2015)
{A novel, N-heterocyclic carbene (NHC) catalyzed direct oxidative coupling of styrenes with aldehydes has been described for the synthesis of alpha,beta-epoxy ketones in good yields. This unprecedented regioselective oxidative coupling employs NBS/DBU/DMSO (DBU = 1,8-diazabicyclo [5.4. 0] undec-7-ene
Keywords: aldehydes; epoxidation; N-heterocyclic carbenes; Oxidation; synthetic methods

One-pot highly enantio- and diastereoselective synthesis of anti,anti vinylic 3-amino-1,2 diols via proline catalyzed sequential alpha-amination/benzoyloxyallylation of aldehydes - Ahuja, Brij Bhushan; Sudalai, Arumugam (RSC Advances, 2015)
The first direct asymmetric synthesis of anti, anti vinylic 3-amino-1,2-diols from aldehydes is described via a one-pot sequential L-proline catalyzed alpha-amination/benzoyloxyallylation protocol. The reaction proceeds with exceptionally high diastereoselectivity (>99%) as can be explained based on the Felkin-Ahn transition state model. Its effectiveness is proven unambiguously by demonstrating a short asymmetric synthesis of D-ribo-phytosphingosine tetraacetate (93% ee).

Organocatalytic [4+1]-annulation approach for the synthesis of densely functionalized pyrazolidine carboxylates - Lalwani, Komal G.; Aher, Ravindra D.; Sudalai, Arumugam (RSC Advances, 2015)
A novel one-pot [4+1]-annulation process for the asymmetric synthesis of densely functionalized pyrazolidine carboxylates is described. The in situ generated gamma-hydrazino-alpha,beta-unsaturated ester obtained via proline catalysis acts as a four-atom component, and Corey's sulfur ylide or ethyl bromoacetate acts as a one-atom carbon source to construct pyrazolidine carboxylate units in a highly enantio- and diastereoselective fashion.

Proline-catalyzed alpha-aminooxylation of beta-amino aldehydes: access to enantiomerically pure syn- and anti-3-amino-3-aryl-1,2-alkanediols - Venkataramasubramanian, V.; Kiran, I. N. Chaithanya; Sudalai, Arumugam (Synlett, 2015)
A new synthetic method for enantioselective synthesis of syn 3-amino-3-aryl-1,2-alkanediols via praline catalyzed alpha-aminaoxn y ylation of beta-amino aldehydes des are described. This methodology is successfully applied to a concise and protecting group-free asymmetric synthesis of (-)-cytoxazone (+)-epi-cytoxazone and formal synthesis of N-thiolated 2-oxazolidinone.
Keywords: amino aldehydes; Asymmetric synthesis; catalysis; diastereoselectivity; Enantioselectivity; Natural product

Proline-catalyzed sequential syn-mannich and [4+1]-annulation cascade reactions to form densely functionalized pyrrolidines - Aher, Ravindra D.; Kumar, B. Senthil; Sudalai, Arumugam (Journal of Organic Chemistry, 2015)
A highly efficient one-pot [4 + 1]-annulation process for the asymmetric synthesis of densely functionalized pyrrolidine derivatives is described. The in situ generated syn-Mannich adduct obtained via proline catalysis acts as a four-atom component, and Coreys sulfur ylide or ethyl bromoacetate acts as a one-atom carbon source to construct pyrrolidine units in a highly enantio- and diastereoselective manner.

Short enantioselective synthesis of ephedrine, amphetamine and their analogues via two stereocentered Co(III)-catalyzed hydrolytic kinetic resolution of racemic syn-benzyloxy epoxide - Lalwani, Komal G.; Sudalai, Arumugam (Tetrahedron Letters, 2015)
An efficient route for the synthesis of 6 drugs belonging to phenethylamine and amphetamine classes in excellent overall yields and high optical purity has been described. The strategy involves introduction of stereogenic centers by means of two-stereocentered Co(III)-catalyzed hydrolytic kinetic resolution (HKR) of racemic syn-benzyloxy epoxide followed by Pd-catalyzed regioselective cationic hydrogenation of amino alcohols as the key reactions. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Amphetamine; Cationic hydrogenation; Hydrolytic kinetic resolution; Phenethylamine; Stereogenic centers

Sodium periodate mediated oxidative transformations in organic synthesis - Sudalai, Arumugam; Khenkin, Alexander; Neumann, Ronny (Organic & Biomolecular Chemistry, 2015)
The investigation of new oxidative transformations for the synthesis of carbon-heteroatom and heteroatom-heteroatom bonds is of fundamental importance in the synthesis of numerous bioactive molecules and fine chemicals. In this context, NaIO4, an exciting reagent, has attracted increasing attention enabling the development of these unprecedented oxidative transformations that are difficult to achieve otherwise. Thus, NaIO4 has been successfully explored as a versatile oxidant for a variety of fundamental organic transformations such as C-H activation, oxidative functionalization of alkenes and other interesting oxidative transformations and its application in the synthesis of bioactive natural products. This review summarizes recent developments in this area with NaIO4 as a versatile oxidant and brings out many challenges that still remain elusive for the future.

Concise enantioselective synthesis of (+)-L-733,060 and (+)-T-2328 via sequential proline catalysis - Lalwani, Komal G.; Sudalai, Arumugam (Synlett, 2016)
A new, sequential proline-catalyzed approach to the synthesis of (+)-L-733,060 and (+)-T-2328 in high optical purity (93% ee) is described starting from phenyl N-Boc imine. The strategy involves proline-catalyzed Mannich reaction of an arylimine with acetaldehyde followed by -aminoxylation/Wittig olefination in a sequential fashion as the key steps.
Keywords: Aminoxylation; imine; Mannich reaction; olefination; sequential

Concise enantioselective synthesis of (+)-sertraline and (-)-CP-52002 using proline catalysis - Kalshetti, Rupali G.; Venkataramasubramanian, V.; Kamble, Sanjay P.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A short enantioselective synthesis of (+)-sertraline and its C-4 epimer (-)-CP-52002 with an overall yield of 30%, respectively, as its hydrochloride has been described. The key steps are the proline catalyzed Mannich reaction of acetaldehyde and acid catalyzed intramolecular Friedel-Crafts' alkylation reaction of olefin proceeding with high optical purities. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Indatraline; Mannich reaction; Proline catalysis; Sertraline; Tametraline

Formal enantioselective synthesis of (-)-epiquinamide by proline-catalyzed one-pot sequential -amination/propargylation of aldehyde and asymmetric dihydroxylation of olefin - Ahuja, Brij Bhushan; Emmanuvel, Lourdusamy; Sudalai, Arumugam (Synlett, 2016)
Two independent routes to the formal synthesis of (-)-epiquinamide, have been described: the first route utilizes an l-proline-catalyzed one-pot sequential -amination/propargylation of aldehyde, while the second one employs asymmetric dihydroxylation as the key reaction to install the stereochemistry. While the first synthesis was accomplished in nine steps with 24.4% overall yield and dr 9:1, the second strategy resulted in the synthesis in eight steps with 36.4% overall yield and with perfect enantiocontrol.
Keywords: Amination; diastereoselective; Dihydroxylation; Proline; quinolizidine

Formal total synthesis of anti-helicobacter pylori agent (+)-spirolaxine methyl ether - Gadakh, Sunita K.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A convergent, formal enantioselective synthesis of anti-Helicobacter pylori agent, (+)-spirolaxine methyl ether 2 has been achieved in high enantiomeric purity starting from commercially available 1,5-pentanediol. The strategy mainly comprises of the Noyori's asymmetric reduction and Brown allylation/Cu-catalyzed lactonization as the key step for the construction of key chiral intermediates, spiroketal 3 and phthalide fragment 4. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Brown allylation; Cu-catalyzed lactonization; Noyori's asymmetric reduction; Phthalide; Spiroketal

I-2-mediated regioselective C-3 azidation of indoles - Prasad, Pragati K.; Kalshetti, Rupali G.; Reddi, Rambabu N.; Kamble, Sanjay P.; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2016)
An unprecedented synthesis of novel 3-azido indoles has been developed using I-2 and NaN3 in high yields and excellent regio-selectivity. The reaction proceeds under metal-free conditions at room temperature. Essentially, an umpolung in reactivity at the C-3 position of indole has been achieved by the activation of indoles with I-2.

N-heterocyclic-carbene-catalyzed regioselective oxidative ring-opening of epoxides with aromatic aldehydes: a facile entry to alpha-acyloxyketones - Reddi, Rambabu N.; Gontala, Arjun; Prasad, Pragati K.; Sudalai, Arumugam (Asian Journal of Organic Chemistry, 2016)
A high-yielding synthesis of -acyloxyketones using a N-heterocyclic-carbene (NHC)-catalyzed, oxidative ring-opening of epoxides with aromatic aldehydes is described. This regioselective, oxidative process utilizes a N-bromosuccinimide (NBS)/DMSO combination as the oxidant system and Et3N as the base under mild reaction conditions.
Keywords: aldehydes; epoxides; halogen oxidants; N-heterocyclic carbenes; oxygen

Organocatalytic route to enantioselective synthesis of ceramide trafficking inhibitor HPA-12 - Lalwani, Komal G.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A new organocatalytic approach to the synthesis of ceramide trafficking inhibitor HPA-12 has been described starting from phenacyl bromide. The strategy involves chiral CBS reduction of gamma-ketoester and proline-catalyzed alpha-amination reaction of aldehyde followed by reduction as the key chirality inducing steps. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: alpha-Amination; CBS reduction; Ceramide; Organocatalytic; Proline

Palladium-catalyzed internal nucleophile-assisted hydration-olefin insertion cascade: diastereoselective synthesis of 2,3-dihydro-1H-inden-1-ones - Vinoth, Perumal; Nagarajan, Subbiah; Maheswari, C. Uma; Sudalai, Arumugam; Pace, Vittorio; Sridharan, Vellaisamy (Organic Letters, 2016)
A novel palladium-catalyzed hydration-olefin insertion cascade assisted by internal nucleophiles was developed for the synthesis of biologically significant 2,3-dihydro-1H-inden-1-ones under mild conditions. A detailed mechanistic study revealed that the assistance of the internal nucleophiles is crucial to trigger the cascade reaction via nucleopalladation of the alkyne moiety. The overall reaction is equivalent to regioselective hydration of alkynes followed by intramolecular Michael addition. This highly efficient and 100% atom-economical domino sequence afforded cis-2,3-disubstituted 2,3-dihydro-1H-inden-1-ones in excellent yields (up to 99%) with complete diastereoselectivity.

Pd-catalyzed reductive cleavage of N-N bond in dibenzyl-1-alkylhydrazine-1,2-dicarboxylates with PMHS: application to a formal enantioselective synthesis of (R)-sitagliptin - Dey, Soumen; Gadakh, Sunita K.; Ahuja, Brij Bhushan; Kamble, Sanjay P.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
An environmentally benign approach involving Pd-catalyzed reductive N-N bond cleavage in dibenzyl-1-alkylhydrazine-1,2-dicarboxylates leading to the synthesis of N-(tert-butoxy)carbamates under very mild conditions has been described. PMHS serves as an inexpensive source of hydride in MeOH/deionized H2O medium. This protocol has been successfully applied in the formal synthesis of (R)-sitagliptin, an anti-diabetic drug. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: anti-Diabetic; Environmentally benign; Hydrazine; PMHS; Reductive cleavage

Proline catalyzed enantioselective synthesis of (2S,3S)-3-hydroxypipecolic acid and formal synthesis of (+)-swainsonine - Aher, Ravindra D.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A short enantioselective synthesis of (2S,3S)-3-hydroxypipecolic acid (overall yield: 18.8%; 96% ee) and formal synthesis of (+)-swainsonine (overall yield: 13.6%; 96% ee) have been described starting from commercially available acrolein. The synthetic strategy involves a high enantioselective L-proline catalyzed sequential c-amination and diastereoselective (dr > 99:1) Barbier allylation of aldehyde in one-pot as the key reaction. (C) 2016 Elsevier Ltd. All rights reserved.

Regioselective oxo-amination of alkenes and enol ethers with N-bromosuccinimide-dimethyl sulfoxide combination: a facile synthesis of alpha-amino-ketones and esters - Prasad, Pragati K.; Reddi, Rambabu N.; Sudalai, Arumugam (Organic Letters, 2016)
An unprecedented conversion of alkenes and enol ethers to the corresponding a-imido carbonyl compounds with excellent regioselectivity and yields has been developed. This oxo-amination process employs readily available N-bromosuccinimide (NBS) and secondary amines as N-sources and dimethyl sulfoxide (DMSO) as the oxidant and also leads to the production of amino alcohols in a single step on reduction, thus broadening the scope of this operationally simple reaction. For the first time, the formation of reactive Me2S+-O-Br species generated by the interaction of NBS with DMSO has been proven.

Concise enantioselective synthesis of 1,4-dideoxy-1,4-imino-D-arabinitol using Co(III)(salen)-catalyzed hydrolytic kinetic resolution of a two-stereocentered anti-azido epoxide - Reddi, Rambabu N.; Prasad, Pragati K.; Kalshetti, Rupali G.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2017)
A concise enantioselective synthesis of 1,4-dideoxy-1,4-imino-D-arabinitol, (+)-DAB-1, has been described in good overall yield (18.1%) and with high enantiomeric purity (up to 98% ee) starting from a simple raw material, cis-2-butene-1,4-diol. The Co-catalyzed hydrolytic kinetic resolution of a two-stereocentered racemic azido epoxide followed by asymmetric dihydroxylation of the alkene and 'one pot' reductive cyclisation of the azido diol are key reactions in the synthetic sequence. (C) 2016 Elsevier Ltd. All rights reserved.

Diastereoselective synthesis of chiral 2,3-disubstituted lndolines via formal [3+2]-cycloaddition of arynes with gamma-amino-alpha,beta-unsaturated esters - Aher, Ravindra D.; Suryavanshi, Gurunath M.; Sudalai, Arumugam (Journal of Organic Chemistry, 2017)
A one step formal [3+2]-annulation protocol for the synthesis of 2,3-disubstituted indolines is described. The in situ generated aryne acts as a two-atom component, and gamma-amino-alpha,beta-unsaturated esters acting as a three-atom component to construct indoline units in a highly regio- and diastereoselective manner with yields ranging from 63 to 80%.

"Metal-free'' synthesis of 1,2,3-triazoles via tandem azidation, intramolecular [3+2]-cycloaddition and aromatization of ethyl acrylate derivatives - Kumar, B. Senthil; Gadakh, Sunita; Sudalai, Arumugam (Tetrahedron Letters, 2018)
An efficient ``one-pot'' method for the synthesis of substituted 1,2,3-triazole derivatives in excellent yields as single regioisomer is reported. The key transformation involves an atom-efficient tandem azidation, intramolecular [3+2]-cycloaddition and aromatization of acrylate derivatives on treatment with NaN3 in DMF under mild conditions. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Intramolecular cycloaddition; Regioselective; Tandem azidation; triazoles

Ni-Catalyzed dimerization and hydroperfluoroarylation of 1,3-dienes - Iwasaki, Takanori; Min, Xin; Fukuoka, Asuka; Zhu, Longzhi; Qiu, Renhua; Yang, Tao; Ehara, Masahiro; Sudalai, Arumugam; Kambe, Nobuaki (Journal of Organic Chemistry, 2018)

Concise formal synthesis of (-)-(6R,11R,14R)-colletallol via D-proline catalysed alpha-aminooxylation-Wittig olefination strategy - Dey, Soumen; Gadakh, Sunita; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
An efficient enantioselective formal synthesis of marine macrolide (-)-(6R,11R,14R)-colletallol has been achieved starting from commercially available raw materials. The key reactions include the D-proline catalyzed a-aminooxylation of aldehyde followed by Horner-Wardsworth-Emmons olefination in a sequential fashion to give the macrolide key intermediate 5 in high enantiomeric purity (97% ee) and high overall yield (32%).
Keywords: alpha-aminoxylation; Asymmetric synthesis; Enantioselectivity; Natural products; organocatalysis

Proline catalyzed sequential alpha-amination/ Prins/ Ritter amidation of aldehydes: new method of construction of tetrahydropyran units - Ahuja, Brijbhushan; Gadakh, Sunita; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
An efficient ``one-pot'' synthetic method toward highly substituted tetrahydrofuran (THP) units is reported. The key transformation involves an atom-efficient sequential proline catalyzed alpha-amination of aldehydes to give alpha-aminated aldehydes in situ and the subsequent cyclomerization with homoallylic alcohols under Prins/Ritter conditions. Notably, this method provides access to enantiopure 1,2-syn and 1,4-anti diamino alcohols via reductive ring opening of THP units.
Keywords: alpha-aminoxylation; organocatalysis; Proline catalyzed; sequential; tetrahydropyran unit

Concise enantioselective synthesis of (R)-(+)-goniothalamin oxide, a trypanocidal active agent via L-prolinol catalyzed asymmetric epoxidation of cinnamaldehyde - Kumar, B. Senthil; Mandle, Ram D.; Kamble, Sanjay P.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2020)
A short and straight-forward enantioselective synthesis of (R)-(+)-goniothalamin oxide 2 has been achieved with an overall yield of 39% and 99% ee. The synthetic approach involves L-prolinol catalyzed asymmetric epoxidation of cinnamaldehyde followed by Lewis acid-mediated diastereoselective allylation of epoxy aldehyde as the key chiral-inducing steps.
Keywords: Allylation; asymmetric epoxidation; Esterification; Grubbs' catalyst; L-prolinol catalyst; Ring closing metathesis

P2O5-mediated Friedel-Crafts acylation of activated arenes with carboxylic acid as acylating agent - Kalshetti, Rupali G.; Mandle, Ram D.; Kamble, Sanjay P.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2020)
P2O5 has been found to be a highly efficient and environmental friendly catalyst for the liquid-phase acylation of activated aromatic substrates giving aromatic ketones (45-93%) in a regioselective manner. Both aromatic and aliphatic carboxylic acids can be employed as acylating source. The process is particularly demonstrated at 100 g scale in the case of anisole and acetic acid to produce 4-methoxyacetophenone.
Keywords: 4-methoxyacetophenone; Carboxylic acid; Friedel-Crafts acylations; phosphorus pentoxide

Triethyl phosphite/benzoyl peroxide mediated reductive dealkylation of O-benzoylhydroxylamines: a cascade synthesis of secondary amides - Aegurla, Balakrishna; Mandle, Ram D.; Shinde, Prasad G.; Parit, Ratan S.; Kamble, Sanjay P.; Sudalai, Arumugam; Senthilkumar, Beeran (European Journal of Organic Chemistry, 2020)
A new triethyl phosphite/benzoyl peroxide (BPO) mediated system has been developed for the synthesis of secondary amides with good to excellent yields in a single step. This unprecedented cascade process involves sequential reduction of N-O bond and benzoylation followed by dealkylation of N-C bond ofO-benzoylhydroxylamines (O-BHA). The methodology is versatile as it tolerates a variety of aromatic and aliphaticO-BHA as substrates to access secondary amides.
Keywords: Amides; Cascade reactions; O-Benzoylhydroxylamines; Redox reactions; synthetic methods

Studies toward the total synthesis of (+)-neopeltolide using N-heterocyclic carbene-catalyzed oxo-acyloxylation/reductive oxa-Michael addition strategy - Reddi, Rambabu N.; Sudalai, Arumugam; Jo, Changbum (Bulletin of the Korean Chemical Society, 2022)
This article describes a concise synthesis of two important fragments (tetrahydropyran [THP] and ketone moieties) of the cytotoxic macrolide (+)-neopeltolide in 10 long linear steps in enantiomerically pure form. Asymmetric Keck allylation to install the required C11 and C13 stereocenters, N-heterocyclic carbene (NHC)-catalyzed oxoacyloxylation to functionalize alkenes, and reductive oxa-Michael addition to construct 2,6-difunctionalized THP unit intramolecularly are the important steps in synthetic efforts. Finally, Keck asymmetric allylation and Lewis acid-catalyzed diastereoselective allylation of the aldehyde were sequentially employed to establish the stereocenters at C11 and C13 positions, respectively.
Keywords: (+)-neopeltolide; Keck allylation; Macrolide; NHC-catalyzed oxoacyloxylation; reductive oxa-Michael addition